2011
DOI: 10.1186/gb-2011-12-4-r33
|View full text |Cite
|
Sign up to set email alerts
|

High recombination rates and hotspots in a Plasmodium falciparum genetic cross

Abstract: BackgroundThe human malaria parasite Plasmodium falciparum survives pressures from the host immune system and antimalarial drugs by modifying its genome. Genetic recombination and nucleotide substitution are the two major mechanisms that the parasite employs to generate genome diversity. A better understanding of these mechanisms may provide important information for studying parasite evolution, immune evasion and drug resistance.ResultsHere, we used a high-density tiling array to estimate the genetic recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
83
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 45 publications
12
83
0
1
Order By: Relevance
“…In addition, in high transmission areas, patients have multiple strain infections transmitted to the mosquito vector. Crossing over of genes during meiosis in the mosquito can then break up resistance and compensatory mutations, and this greater opportunity for recombination will result in increased parasite diversity and direct competition between different parasite strains, with less opportunity for resistant alleles to become fixed (Jiang et al 2011;Takala-Harrison and Laufer 2015). This is not the case in low transmission areas where multiple infections are much less common, infected individuals are less preimmune, usually more prone to be symptomatic, and, as a consequence, to be treated with possible poor-quality antimalarial drugs, incomplete treatment courses, or (artemisinin) monotherapies.…”
Section: Origins Of Antimalarial Drug Resistancementioning
confidence: 99%
“…In addition, in high transmission areas, patients have multiple strain infections transmitted to the mosquito vector. Crossing over of genes during meiosis in the mosquito can then break up resistance and compensatory mutations, and this greater opportunity for recombination will result in increased parasite diversity and direct competition between different parasite strains, with less opportunity for resistant alleles to become fixed (Jiang et al 2011;Takala-Harrison and Laufer 2015). This is not the case in low transmission areas where multiple infections are much less common, infected individuals are less preimmune, usually more prone to be symptomatic, and, as a consequence, to be treated with possible poor-quality antimalarial drugs, incomplete treatment courses, or (artemisinin) monotherapies.…”
Section: Origins Of Antimalarial Drug Resistancementioning
confidence: 99%
“…Analyses of parasite populations (119) and genetic crosses (74,77) showed that the subtelomeric regions have a high rate of recombination during the sexual stages. Further studies are needed to ascertain whether these events occur during meiosis or the numerous subsequent mitotic divisions in the mosquito vector.…”
Section: Subtelomeric Regions and Antigenic Diversificationmentioning
confidence: 99%
“…Several other studies, nonetheless, have explored outcomes of meiotic recombination. P. falciparum genetic cross studies have analyzed the segregation of chromosomal markers (SNPs and microsatellites) spread out over the genome between geographically distinct parasite clones: 3D7 ϫ HB3 (79), HB3 ϫ Dd2 (73,74,(80)(81)(82), and 7G8 ϫ GB4 (77,83,84). These were instrumental in mapping the dihydrofolate reductase gene (dhfr) (85) and P. falciparum chloroquine resistance transporter gene (pfcrt) (86) that are key drug resistance loci and identifying key determinants of host cell tropism (77,83,84).…”
Section: Meiotic Recombination: Mechanisms and Evidence In P Falciparummentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic mapping and hotspot identification have also been performed in Plasmodium spp. (30)(31)(32)(33). Previously, our laboratory identified and investigated the role of molecules involved in HR.…”
mentioning
confidence: 99%